Lower Extremity Biomechanics Are Altered Across Maturation in Sport-Specialized Female Adolescent Athletes - DiCesare, Christopher A.; Montalvo, Alicia; Barber Foss, Kim D.; Thomas, Staci M.; Ford, Kevin R.; Hewett, Timothy E.; Jayanthi, Neeru A.; Stracciolini, Andrea; Bell, David R.; Myer, Gregory D. (Frontiers in Pediatrics, 2019)
Sport specialization is a growing trend in youth athletes and may contribute to increased injury risk. The neuromuscular deficits that often manifest during maturation in young, female athletes may be exacerbated in athletes who specialize in a single sport. The purpose of this study was to investigate if sport specialization is associated with increased lower extremity biomechanical deficits pre- to post-puberty in adolescent female athletes. Seventy-nine sport-specialized female adolescent (Mean ± SD age = 13.4 ± 1.8 years) basketball, soccer, and volleyball athletes were identified and matched with seventy-nine multi-sport (soccer, basketball, and volleyball) female athletes from a database of 1,116 female adolescent basketball, soccer, and volleyball athletes who were enrolled in one of two large prospective, longitudinal studies. The athletes were assessed over two visits (Mean ± SD time = 724.5 ± 388.7 days) in which they were classified as pre-pubertal and post-pubertal, respectively. Separate 2 × 2 analyses of covariance were used to compare sport-specialized and multi-sport groups and dominant/non-dominant limbs with respect to pubertal changes in peak knee sagittal, frontal, and transverse plane joint angular measures and moments of force recorded while performing a drop vertical jump task. The sport-specialized group were found to exhibit significantly larger post-pubertal increases in peak knee abduction angle (p = 0.005) and knee abduction moment (p = 0.006), as well as a smaller increase in peak knee extensor moment (p = 0.032) during landing when compared to the multi-sport group. These biomechanical changes are indicative of potentially compromised neuromuscular control that may increase injury risk pre- to post-puberty in sport-specialized female athletes. Consideration of maturation status may be an important factor in assessing the injury risk profiles of adolescent athletes who specialize in sport.